Adherence in children using positive airway pressure therapy: a big-data analysis. Issue 2 (February 2020) - Bhattacharjee, Rakesh; Benjafield, Adam V; Armitstead, Jeff; Cistulli, Peter A; Nunez, Carlos M; Pepin, Jean-Louis D; Woehrle, Holger; Yan, Yang; Malhotra, Atul; ,
Summary: Background: Positive airway pressure (PAP) has become a prominent treatment for children with sleep-disordered breathing. However, there are no large-scale studies to clarify whether PAP is well tolerated in children, and which factors are associated with better adherence to PAP therapy. In this study, we aimed to clarify adherence patterns of PAP therapy in a large paediatric population. Methods: We did a cross-sectional big-data analysis in children from Oct 1, 2014, to Aug 1, 2018, using existing data derived from PAP devices uploaded nightly in the AirView cloud database. The AirView database is a usage tracking system available to all patients who are assigned PAP therapy, which requires consent from the patient or parent or guardian. All patients older than 4 years and younger than 18 years who used continuous or automated PAP devices were evaluated. Only patients living in the USA and enrolled with a single insurance company were included. If patients were participating in an engagement programme, programme onset must have been within 7 days of therapy onset. Our primary outcome was the proportion of patients who used PAP continuously over 90 days. The primary outcome was assessed in all patients who met the age inclusion criterion and had reliable age data available. Data on missing PAP use were imputed as zero, but data on other metrics were not imputed and excluded from analysis. Findings: We used data recorded from Oct 1, 2014, to Aug 1, 2018. Of 40 140 children screened, 36 058 (89·8%) were US residents and 20 553 (90·1%) of them met the eligibility criteria and had accessible data (mean age 13·0 years [SD 3·7]). On the basis of 90 days of monitoring data, 12 699 (61·8%) patients continuously used PAP. Factors significantly associated with adherence included age group, residual apnoea–hypopnoea index, use and onset of patient engagement programmes, PAP pressure, and nightly median PAP mask leak, all over the 90-day study period. Interpretation: To our knowledge, our study represents the largest analysis of children using PAP therapy to date. The findings suggest that adherence to PAP therapy is lower than in previous reports from adults. However, numerous actionable factors were associated with improvements in adherence and should be used strategically in clinical decision making to improve PAP adherence in children. Funding: ResMed.